Effects of additive mixtures (THF/SDS) on carbon dioxide hydrate formation and dissociation in porous media - Yang, Mingjun; Song, Yongchen; Liu, Weiguo; Zhao, Jiafei; Ruan, Xuke; Jiang, Lanlan; Li, Qingping (Chemical Engineering Science, 2013)
The characteristics and stability conditions of carbon dioxide (CO2) hydrate formation are crucial for hydrate-based CO2 capture and storage. The effects of a mixture of additives (THF/SDS) on CO2 hydrate formation and dissociation in porous media have been investigated experimentally using a graphic method. The Gibbs phase rule is used to analyze the experimental p-T curves. Hydrate formation processes can be divided into two cases, depending on the CO2 initial state. The experimental results showed that 1000 mg/L SDS is the best additive and concentration for CO2 hydrate formation among those studied in this investigation due to its shorter induction time and resultantly higher hydrate saturation than those of other concentrations. The presence of 3 mol% THF dramatically decreased the hydrate phase equilibrium pressure. The hydrate equilibrium temperature is 291.55 K in the aqueous phase with 3 mol% THF and 0 mg/L SDS, which is the highest equilibrium temperature at 3.04 MPa observed in this investigation. The experimental results also showed that "pseudo-retrograde" behavior exists at nearly 3.00 MPa with all SDS concentrations. An improved model is used to predict the phase equilibrium conditions for CO2 hydrates in glass beads in the presence of THF, in which the mechanical equilibrium of force between the interfaces in a hydrate-liquid-vapor system is considered. (C) 2012 Elsevier Ltd. All rights reserved.